The Impact of Earnings Management, Leverage, and Profitability on Tax Avoidance in Mining Sector Companies - Diah Intan Syahfitri; Novida Halleine Putri (Komunitas Dosen Indonesia, 2024)
Taxes help the country develop in education, health, industry, and more. Since taxes are a major source of state revenue, the government prioritizes tax payment. Industrial taxpayers should follow appropriate norms and correct accounting principles to avoid violating government or country tax legislation. This research aims to study and assess the influence of profitability, leverage and earnings management on tax avoidance in mining companies listed on the Indonesia Stock Exchange (BEI). The focus of this research is on the group of companies in the mining sector listed on the BEI during the period 2019 to 2023. A saturated sampling technique, or often referred to as a census, is used in this research, where all 62 companies in the population are included as samples for a continuous period of 5 years. , resulting in a total of 310 observations. The results of hypothesis testing show that the earnings management, leverage and profitability variables together have a significant influence on tax avoidance. Earnings management, leverage, and profitability each have a large and positive impact on tax avoidance practices. This research is aimed at providing valuable insights and a complete understanding of tax evasion, with the aim of assisting stakeholders, including the government, in making the right decisions and formulating effective tax control laws.